2012
DOI: 10.1155/2012/509694
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Heterotopic Pregnancy, Simultaneous Ovarian, and Intrauterine: A Case Report

Abstract: Spontaneous heterotopic pregnancy is a rare clinical condition in which intrauterine and extrauterine pregnancies occur at the same time. The occurrence of an ovarian heterotopic pregnancy is a singular event as it comprises only 2.3% of all heterotopic pregnancies, extremely rare among women who conceive naturally. A case of a 28-year old patient was treated for spontaneously conceived heterotopic pregnancy. The patient was admitted to our center with lower abdominal pain and amenorrhoea. A transvaginal ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 9 publications
(9 reference statements)
0
36
0
9
Order By: Relevance
“…Missed HP also has reported by Kratschla-Apochal et al and Gibson Kyle et al [9,10]. Nevertheless, it was earlier detected in other series [11,12].…”
Section: Commentmentioning
confidence: 63%
“…Missed HP also has reported by Kratschla-Apochal et al and Gibson Kyle et al [9,10]. Nevertheless, it was earlier detected in other series [11,12].…”
Section: Commentmentioning
confidence: 63%
“…It is notable, however, that HP can occur in patients with a beta hCG as low as 125 mIU/mL 10. Assisted reproductive technology has increased in recent decades and so has HP, thus clinicians should take good reproductive histories with this correlation in mind 11. The case presented here represents an occasion where the clinician must take a careful history and perform a very thorough physical examination.…”
Section: Discussionmentioning
confidence: 91%
“…A review study showed that most of extrauterine pregnancies were located in the fallopian tube (72.5%). 9 An ovarian HP is a rare diagnosis with few reported cases. A review literature found only 5 cases of ovarian HP which were spontaneous, while most of them were following clomiphene or ART use.…”
Section: Discussionmentioning
confidence: 99%